2022
DOI: 10.1039/d1tc04763a
|View full text |Cite
|
Sign up to set email alerts
|

Design of efficient color-tunable long persistent luminescence phosphor BaGa2O4:Pr3+ and its performance enhancement via a trap-induced strategy

Abstract: Color-tunable long persistent luminescence (LPL) phosphors are more strongly desired for intelligent anti-counterfeiting and information storage compared with single color types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…The deconvoluted high-energy peaks, centered at 531.36 eV in LZPM 0.14 and 531.40 eV in LZPM 0.14 -H, can be both ascribed to the presence of V O . 54,55 The same conclusion can be drawn from the EPR spectra of V O as well (Fig. 2c).…”
Section: Temperature-dependent Photoluminescent Properties Of Lzpm Xsupporting
confidence: 81%
“…The deconvoluted high-energy peaks, centered at 531.36 eV in LZPM 0.14 and 531.40 eV in LZPM 0.14 -H, can be both ascribed to the presence of V O . 54,55 The same conclusion can be drawn from the EPR spectra of V O as well (Fig. 2c).…”
Section: Temperature-dependent Photoluminescent Properties Of Lzpm Xsupporting
confidence: 81%
“…S6, ESI†), approaching that of other gallate compounds, such as ZnGa 2 O 4 (∼5 eV), LiGaO 2 (∼5.26 eV), and BaGa 2 O 4 (∼5.8 eV). 43–45 The DFT calculations, using the modified Becke–Johnson (mBJ) method, yield a theoretical bandgap of 5.6 eV (Fig. S7, ESI†), identical to the experimental value.…”
Section: Resultssupporting
confidence: 54%
“…In recent years, the design and modulation of phosphors by replacing anions or ionic groups with solid solution have become one of the research hotspots. Denalt et al found that the luminescence performance of Ba 2− x Sr x SiO4:Eu 2+ samples could be substantially improved by using the substitution of the same main group ion Sr 2+ in Ba 2 SiO 4 :Eu 2+ , which is because Sr 2+ substitution increased the thermal stability of phosphors and produced a more rigid crystal structure; 20 Xia pointed out that the the fluorescence performance of Ca 2 (Al 1− x Mg x )(Al 1− x Si 1+ x )O 7 :Eu 2+ could see significant improvements by replacing the [Al 3+ –Al 3+ ] structural unit with [Mg 2+ –Si 4+ ] to facilitate the electron–phonon coupling effect; 21 Lin et al substituted CaYAlO 4 :Eu 2+ ,Eu 3+ phosphors with [Si 4+ –Al 3+ ], [Ca 2+ –Y 3+ ] to make the octahedral lattice of AlO 6 shrink and the polyhedral lattice of CaO 9 expand, so that some of the Eu 3+ ions are reduced to Eu 2+ and the luminous color of the samples is adjustable; 22 Zhou noted that the near-infrared spectrum coverage of BaMgGa x Al 10− x O 17 :Cr 3+ was greatly enhanced through the solid solution with Ga 3+ and Al 3+ and the half-peak width increased from 100 nm to 300 nm, and the substitution of Ga 3+ for Al 3+ led to an increase in CrO bond stress, a decrease in the bond length and an increase in energy level cleavage, resulting in a significant improvement in the optical properties of the sample; 23 Ma et al investigated a 2000% increase in initial afterglow luminance and 350% increase in afterglow time in the BaGa 2− x Zn x O 4 :Pr 3+ series of samples; 24 Xie found that the trap depth of Y 3 Al 5− x Ga x O 12 :Ce 3+ ,V 3+ ( x = 0–3) could be adjusted by solid solution of Al 3+ by Ga 3+ , resulting in the change of the crystal field intensity. Meanwhile, the solid solution of Ga 3+ led to the adjustment of the luminescence color of the sample from green to yellow, which has a good application prospect for optical storage.…”
Section: Introductionmentioning
confidence: 99%